2009
DOI: 10.1186/1751-0147-51-39
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal acidosis and the rapid onset of ruminal parakeratosis in a mature dairy cow: a case report

Abstract: A mature dairy cow was transitioned from a high forage (100% forage) to a high-grain (79% grain) diet over seven days. Continuous ruminal pH recordings were utilized to diagnose the severity of ruminal acidosis. Additionally, blood and rumen papillae biopsies were collected to describe the structural and functional adaptations of the rumen epithelium. On the final day of the grain challenge, the daily mean ruminal pH was 5.41 ± 0.09 with a minimum of 4.89 and a maximum of 6.31. Ruminal pH was under 5.0 for 130… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
6
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(127 citation statements)
references
References 15 publications
7
108
6
6
Order By: Relevance
“…The similarity of the alterations in ruminal epithelial structure during long-term HG diet feeding to that reported in acid-treated RE in vitro suggests that the ruminal acidosis may be the major insult leading to ruminal epithelial structural lesions. However, our results are somewhat inconsistent with other in vivo studies that found dramatic RE structural adaptations, indicative of ruminal parakeratosis, while no impairment of the deeper cell layers and cellular necrosis during a short exposure (did not exceed 21 days) to a HG diet in dairy cows and lambs (35)(36)(37). This discrepancy might be related to differences in feeding time.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The similarity of the alterations in ruminal epithelial structure during long-term HG diet feeding to that reported in acid-treated RE in vitro suggests that the ruminal acidosis may be the major insult leading to ruminal epithelial structural lesions. However, our results are somewhat inconsistent with other in vivo studies that found dramatic RE structural adaptations, indicative of ruminal parakeratosis, while no impairment of the deeper cell layers and cellular necrosis during a short exposure (did not exceed 21 days) to a HG diet in dairy cows and lambs (35)(36)(37). This discrepancy might be related to differences in feeding time.…”
Section: Discussioncontrasting
confidence: 99%
“…It should be acknowledged that any one or the combination of these factors may affect epithelial barrier function. In addition, the prominent histological alterations during HG feeding strongly suggest an impaired barrier function (35)(36)(37) that may provide the opportunity for the translocation of toxins and bacteria from the rumen into the blood, ultimately affecting animal health and productivity (28). Although there is fundamental knowledge about the consequences of HG feeding on ruminal epithelial barrier function, remarkably little information is currently available about the underlying molecular changes in ruminal epithelial barrier function during HG diet feeding.…”
mentioning
confidence: 99%
“…On the other hand, the heavy rumens observed in concentrate-fed animals (regardless of the amount of straw included in the TMR) could also be caused by the stimulant effect that feeding concentrate has on ruminal development (Odongo et al, 2006). However, it must be borne in mind that the rumen wall undergoes structural changes in response to the inflammation process (rumenitis and parakeratosis) associated with high acid load and low pH (Krehbiel et al, 1995;Steele et al, 2009 and.…”
Section: Digestive Tract Characteristicsmentioning
confidence: 99%
“…Por essa razão e visando maior eficiência alimentar dos animais confinados, os produtores de ovinos utilizam dietas que contenham grãos que sejam rapidamente fermentáveis no rúmen, para maximizar a ingestão de energia (BROWN et al, 2006;STEELE et al, 2009).…”
Section: Introductionunclassified
“…As manifestações clínicas da acidose metabólica incluem a depressão no consumo de ração, laminite, abscessos de fígado nos casos crônicos, ruminite e alterações extensas da microbiota ruminal e seus produtos da fermentação, além de lesões na mucosa do rúmen (RESENDE JÚNIOR et al, 2006;STEELE et al, 2009).…”
Section: Introductionunclassified